Implementing Lean Practices: Managing the Transformation Risks. (18th December 2013) - Pearce, Antony; Pons, Dirk
Abstract : Insightful implementation of lean is necessary for high-value manufacturing and is complementary to strategic decision making regarding manufacture. However lean can be difficult to implement in specific organisations. One of the difficulties is deciding which of the many lean tools to apply and when to apply them. A complicating factor is change management. Lean implementation is a transformational process and needs to support organisational development alongside process improvement. We develop a method based on risk management to identify which lean tools are most appropriate for a specific organisational setting. This permits the situational and contingency variables to be accommodated in the lean transformation. The method is demonstrated by application to a small manufacturing organisation with a high-variety low-volume business model. Thus it is possible, given contextual knowledge of the organisation, to predict which lean methods are most important in the situation. This enables the prioritisation of organisational effort towards lean methods that are relevant to the organisation at that particular time in its development.